2015
DOI: 10.1162/jocn_a_00755
|View full text |Cite
|
Sign up to set email alerts
|

Theta Oscillations Modulate Attentional Search Performance Periodically

Abstract: Visual search--finding a target element among similar-looking distractors--is one of the prevailing experimental methods to study attention. Current theories of visual search postulate an early stage of feature extraction interacting with an attentional process that selects candidate targets for further analysis; in difficult search situations, this selection is iterated until the target is found. Although such theories predict an intrinsic periodicity in the neuronal substrates of attentional search, this pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
185
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(202 citation statements)
references
References 38 publications
16
185
0
1
Order By: Relevance
“…Action and visual attention are strongly linked [28][29][30][31] and attention can reset the phase of the ongoing activity in visual areas, or exert an oscillatory gain of the sensory processing [32][33][34][35]. However, visual attention was clearly allocated also in the random-HL condition in experiment 1.…”
Section: Discussionmentioning
confidence: 85%
“…Action and visual attention are strongly linked [28][29][30][31] and attention can reset the phase of the ongoing activity in visual areas, or exert an oscillatory gain of the sensory processing [32][33][34][35]. However, visual attention was clearly allocated also in the random-HL condition in experiment 1.…”
Section: Discussionmentioning
confidence: 85%
“…To study the role of areas involved in attentional processing, TMS has primarily been used in conjunction with visual search [1014] and has shown that visual areas receive feedback information from fronto-parietal areas, at post-stimulus delays ≥150 ms. These studies did not explicitly manipulate attention and thus inferred its role in visual search; however, such inference is not warranted—before invoking an attentional explanation, it is important to rule out the effect of visual and physiological factors (e.g., retinal eccentricity and cortical magnification) and to explicitly manipulate attention [1517].…”
Section: Resultsmentioning
confidence: 99%
“…Covert spatial attention samples visual information periodically at low frequencies, theta (5–7 Hz) and alpha (8–12 Hz), in detection or discrimination tasks [14, 2429]. The authors of these studies suggested that this periodicity indicates that attention processes multiple stimuli sequentially, i.e., attention in these tasks is reoriented to different locations, following a low-frequency rhythm.…”
Section: Resultsmentioning
confidence: 99%
“…For the search task, observers had to report the presence or absence of a target shape T embedded among distracting L shapes. For consistency with another series of transcranial magnetic stimulation-EEG experiments suggesting that attentional difficult search is modulated periodically in time (15), the four shapes were presented at constant eccentricity (8.2°of visual angle) in either the bottom-right or bottomleft quadrant of the screen. Having all search items within a single hemifield also prevented the possible use of "independent" attentional resources for each hemifield (27).…”
Section: Methodsmentioning
confidence: 93%
“…It has been proposed that attention samples visual stimuli periodically rather than continuously (13)(14)(15)(16)(17)(18). This question is connected to the uniform vs. nonuniform debate in that the nonuniform (or sequential) model of attention processing maps rather naturally onto a periodic sampling of visual information (with the periodicity reflecting the switching between stimuli).…”
mentioning
confidence: 99%